Frontline healthcare workers' experiences of providing care during the COVID-19 pandemic at a COVID-19 centre in Bulawayo, Zimbabwe: A phenomenological study - Idah Moyo; Azwihangwisi H. Mavhandu-Mudzusi; Clara Haruzivishe (AOSIS, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has had a far-reaching, negative impact on healthcare systems worldwide. Healthcare workers play a critical role in the country's healthcare delivery system, as they facilitate a continuum of care and containment of diseases such as the COVID-19 pandemic. Objectives: The aim of this study was to explore and describe the experiences of healthcare workers who provided care to COVID-19 patients at a central hospital in Zimbabwe. Method: The researchers used an interpretative phenomenological analysis design. In-depth interviews were conducted virtually with 10 frontline healthcare workers working at a COVID-19 centre in Zimbabwe. Data collection was guided by an interview guide. All audio-recorded interview data were transcribed verbatim into written text. Data analysis was conducted using an interpretative phenomenological analysis framework. An expert in qualitative research acted as an independent co-coder and conducted the open coding of each transcript. Results: Findings reveal inadequate preparation and training of healthcare providers before the commencement of duty, resources-related challenges and a lack of support as significant experiences of healthcare providers. Moreover, healthcare providers have been subjected to stigma and discrimination attached to COVID-19, resulting in psychological effects on frontline healthcare providers. Conclusion: The COVID-19 pandemic brings unique and challenging experiences for frontline healthcare workers, resulting in a physically and emotionally drained workforce. This study calls for comprehensive support in the form of counselling, reasonable work schedules, training and adequate provision of personal protective equipment.